Over-the-counter mouthwash use, nitric oxide and hypertension risk. (3rd March 2020) - Joshipura, Kaumudi; Muñoz-Torres, Francisco; Fernández-Santiago, Jeanpaul; Patel, Rakesh P.; Lopez-Candales, Angel
Abstract: Purpose: Mouthwash is used by a large population. Short-term clinical trials have shown that antibacterial mouthwash deplete oral nitrate-reducing bacteria, and decrease systemic nitric oxide bioavailability. Our previous publication from the San Juan Overweight Adults Longitudinal Study (SOALS) was the first to show frequent over-the-counter mouthwash use was independently associated with increased risk of prediabetes/diabetes. This manuscript evaluates whether over-the-counter mouthwash was associated with increased risk of hypertension. Materials and methods: SOALS recruited 40-65 year old overweight/obese individuals; baseline evaluations started in 2011 and the 3-year follow-up exam was completed by 2016. From the 1028 participants (76%) who completed follow-up, we excluded people with reported physician diagnosis of hypertension or systolic or diastolic BP at or above the hypertension cut-offs ( n  = 481), missing smoking ( n  = 1), missing physical activity ( n  = 1) and missing alcohol intake ( n  = 5) at baseline; 540 participants were included. The primary exposure was mouthwash use twice daily or more. The primary outcome for this manuscript is self-reported physician-diagnosed hypertension over the follow-up. We used Poisson regression controlling for age, sex, smoking, physical activity, waist circumference, alcohol intake, systolic blood pressure, pre-diabetes/diabetes status and cardiac medication use. We additionally evaluated other mouthwash use categorizations. Results: Twelve percent (66/540) developed hypertension over follow-up. People who used mouthwash twice/day or more had higher incidence of hypertension compared to less frequent users (Incidence Rate Ratio = 1.85; 95% Confidence Interval: 1.17, 2.94), and compared to non-users (IRR = 2.17; 95% CI: 1.27, 3.71). Several additional potential confounders evaluated did not impact these associations. Associations persisted among never smokers. Additional outcomes including BP assessed at a single study visit did not show associations. Conclusion: In this study, frequent regular use of over-the-counter mouthwash was associated with increased risk of hypertension, independent of major risk factors for hypertension and several other potential confounders.